(untitled) (Experimental biology, 2017)
In the result of doing work has appointed determinant biological and technological compatibly of 3 lactobacillus strains. Was composed the composition of 3 lactobacillus strains: composition L.fermentum AK-2R, L.acidophilus AA-1, L.plantarum AP-1. Strains of which differentiated for antagonistic activity was extensions in composition. It extend spectrum of consortium probiotical effect.